Qur'anic Values in Sundanese Culture: A Study of Politeness Principles in Paribasa - Hidayatullah, Asep; Anshori, Dadang S.; Sastromiharjo, Andoyo (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
This study investigates the principles of linguistic politeness in the Sundanese language as a reflection of Qur'anic values. The method employs a qualitative approach through content analysis. The research reveals that the politeness principles embedded in Sundanese paribasa align with Qur'anic teachings. These include the concepts of qaulan ma’rufa  (good words), qaulan sadida (truthful words), qaulan baligha (effective words), qaulan karima (noble words), qaulan layyina (gentle words), and qaulan maysura (clear words). These principles highlight the significance of respectful communication, consideration for others' feelings, and promoting harmony within social relationships. Consequently, the politeness observed in Sundanese paribasa serves as a manifestation of Qur'anic teachings in daily social interactions. The findings of this research also enhance the understanding of how local religious and cultural values can synergistically contribute to the development of polite and harmonious communication practices. The novelty of this study lies in its integration of linguistic politeness, rooted in cultural values and Qur'anic principles. It serves as a model for fostering ethical and courteous communication in contemporary society.